Soft Violence, Social Radicalisation, and Violent Transnational Social Movements (VTSMs) - Candyce Kelshall (The Journal of Intelligence, Conflict and Warfare, 2021)
On November 25, 2020, Candyce Kelshall presented on the topic of Soft Violence, Social Radicalisation, and Violent Transnational Social Movements (VTSMs), at the 2020 CASIS West Coast Security Conference. Primary discussion topics included the distinction between terrorists and violent extremists, weapons used by violent extremists, social radicalisation and self actualisation (SRSA), the production of lone actors, and the intersectionality of violent extremist actors. This presentation was followed by a group panel for questions and answers, whereby conference attendees were provided with an opportunity to engage in discussion with Professor Kelshall and the other presenters.